Peningkatan Kemampuan Motorik Kasar Dengan Modifikasi Permainan Bola Voli Siswa Tunagrahita Ringan - Luthfie Lufthansa; Hendi Imam Fadoli; Laila Nur Rohmah; Rizki Kurniati; Bertika Kusuma Prastiwi; Agus Anis Riyanto (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
One way that mild mentally retarded children have good gross motor skills and perform good movement activities is through adaptive physical education learning with game modifications. Therefore, it is necessary to make modifications to the volleyball game that can improve gross motor skills. The method used is research & development by Borg & Gall. The instrument used is an assessment using 2 scales consisting of according to the value of 1 (one) and not in accordance with the value of 0 (zero). Where this assessment is assessed by homeroom teachers, learning experts and volleyball experts. With a small group trial subject, namely class IV students, totaling 10 students. While the subject of the large group trial, namely students in grades V-VI, totaled 23 students. The product of this development is a game modification for mild mentally retarded children which contains 8 models of the